Changes in ocular factors according to depth variation and viewer age after watching a three-dimensional display. Issue 5 (23rd January 2014) - Yum, Hae Ri; Park, Shin Hae; Kang, Hang-Bong; Shin, Sun Young
Abstract : Objective: To investigate changes in ocular factors according to the binocular disparity in three-dimensional (3D) images and age after watching 3D display. Methods: A total of 38 volunteers were enrolled, and they watched a 3D display with a 1° or 3° disparity for 30 min at an interval of 1 week. The near point of accommodation (NPA), near point of convergence (NPC) and tear break-up time (tBUT) of each subject were measured before and after watching the 3D display. In addition, the tear meniscus height and depth were measured using Visante optical coherence tomography and tear osmolarity was measured using TearLab osmometer. A survey of subjective symptoms was also conducted. Results: NPA and NPC increased after watching the 3D display (p<0.05). NPC and NPA increased more in the 40s–50s group (ie, subjects aged in their 40s and 50s) than in the 20s–30s group (ie, subjects aged in their 20s and 30s) after watching 3D content with a 3° disparity (p<0.05). tBUT and tear meniscus height and depth decreased after watching 3D content (p<0.05). They decreased more in the 40s–50s group than in the 20s–30s group after watching 3D content with a 3° disparity (p<0.05). Recovery times of NPA and NPC were significantly greater after watching 3D content with a 3° disparity and in the 40s–50s group (p<0.05). Conclusions: Watching a 3D display affects accommodation and convergence abilities and tear dynamics in a transient fashion, especially in the case of 3D images with a large binocular disparity, and in older subjects. These results provide helpful information for establishment of guidelines for 3D equipment manufacturers.